انتشار الربو التحسسي في منطقة الساحل السوري - سلمان حسين (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة على 1116 مريضاً بالربو القصبي ممن راجعوا الوحدة المهنية التابعة لجامعة تشرين في الفترة الواقعة بين 10/5/2000 و12/9/2004، منهم 562 من النساء متوسط أعمارهن 4, 22 عاماً و554 من الذكور متوسط أعمارهم 3, 21 عاماً. بلغت نسبة مرضى الربو التحسسي 76, 66 % من مجموع مرضى الدراسة، بينما شكلت النسبة الباقية (24, 33 %) من الأشكال الأخرى للربو، حيث احتلت الأسباب الإنتانية المرتبة الأولى في هذه المجموعة (5, 53 % )، تلتها الحالات مجهولة السبب بنسبة (8, 22 %)، فالأسباب المهنية (2, 12 % )، ثم الأسباب الداخلية (1, 4 %) فالربو الدوائي (3 %). أكبر نسبة تحسس كانت من D.pteronyssinus (23, 85 %) ومن D.farinae (2, 79 %) تلاها التحسس من غبار الطلع بنسبة (3,44 %) ، ثم التحسس من الحيوانات المنزلية (9, 21 %) فالتحسس من العفن المنزلي (4,14%). وتأتي أهمية هذه الدراسة من فرز الحالات التي تحسس فيها المرضى من أكثر من عامل محسس واحد، فقد تحسس 18, 46 % من مرضى مجموعة الربو التحسسي من اثنين أو أكثر من العوامل المحسسة، بينما تحسس فقط من D.pteronyssinus و / أو D.farinae 23, 45 % ، من غبار الطلع فقط 19, 8 % ومن العفن المنزلي 4, 0 % من مرضى هذه المجموعة، ولم تسجل أية حالة تحسس منعزلة من وبر الحيوانات المنزلية. ولهذه النتائج أهميتها البالغة في تقدير عدد الحالات الأكثر استجابة للمعالجة المناعية، حيث تقل فرص الحصول على نتائج علاجية بهذه الطريقة مع ازدياد عدد العوامل المحسسة عند المريض الواحد. الملفت في هذه الدراسة أيضاً النسبة العالية للتحسس من D.farinae عند 2, 79 % من مرضى مجموعة الربو التحسسي، وهي نسبة تتجاوز بكثير النسبة المسجلة في المناطق الداخلية من سوريا والتي كانت 7, 1 % في إحدى الدراسات. The research was done on 1116 bronchial asthma patients who visited the professional unit which belongs to Tishreen University from 10/5/2000 to 12/9/2004, 562 of whom were women of average age 22,4 years and 554 men of average age 21,3 years. The percentage of the allergic asthma patients is 66,76 % out of the total patients (1116 ). The rest (33,24 %) suffered from other kinds of asthma, where the severe inflammation occupied 53,5 % of this group, followed by cases which had unknown causes of a percent 22,8 %, then the professional causes 12,2 %, then the internal causes 4,1 %, then asthma caused by medicines 3 %. The largest percent was from D. pteronyssinus (85,23 %) and from D. farinae (79,2 % ), followed by the allergy caused by pollen of a percent 44,3 %, then the allergy caused the fluff of home animals of a percent 21,9 %, then the allergy caused by moulds 14,4 %. The imprtance of this research comes from sorting the cases in which the patients have had allergy from more than one factor that causes allergy. 46,18 % of the patients who suffered from allergic asthma have allergy because of one or tow of the allergic factors, while 45,23 % had only allergy from D. pteronyssinus or D.farinae, and 8,19 % only from pollen,and 0,4 % only from moulds from this group. No case of isolated case of allergy from the animals fluff was recorded. These results have their great importance in estimating the number of the most responded cases for immuned treatment, where the chance of getting treatment results is decreasing in this method with the increasing of the allergic factors for the same patient. What attracts us in this research is the high percentage of the allergy of D. farinae (79,2 %) from the group of the allergic asthma, and this percent very much exceeds the percent recorded in the internal areas in Syria which was 1,7 % in one of the researches.